Combination of bulk laxative along with probiotics and prebiotics in the management of irritable bowel syndrome with constipation: A safe & effective option - Faruqui, Arif Ahmed; Jamaiwar, B; Sharma, B (Asian Journal of Medical Sciences, 2017)
Background: Irritable bowel syndrome (IBS) is a common and relapsing functional bowel disorder. This disease has a substantial global burden and is associated with significant disability and high costs that adversely affects the health related quality of life of large population worldwide. Aims and Objective: We studied the efficacy and tolerability of bulk laxative plus probiotic and prebiotic in the treatment of constipation associated IBS (IBS-C) in Indian patients. Materials and Methods: Eighty patients with symptoms of IBS-C were enrolled in a post-marketing surveillance, multicentre, open label, non-randomized, noncomparative study where EVAQ- P - combination of fiber (psylliun husk/Ispaghula, probiotic and prebiotic) was given BID for 6 weeks. The symptoms were assessed at baseline, and after completion of 2, 4 and 6 weeks of therapy. Results: Results showed a signifi cant trend (p < 0.0001) of improvement from week 2 for abdominal pain, abdominal fullness, defecation frequency, straining during defecation, constipation and subject global assessment of relief (SGA). Approximately 6% patients showed fl atulence (mild) as a treatment emergent side effect. Conclusion: Combination of ispaghula along with a blend of probiotics and prebiotic twice daily for 6 weeks is effi cacious, safe, and well-tolerated in IBS-C patients. Asian Journal of Medical Sciences Vol.8(1) 2017 85-90